“No place like home”: the plight of low-income earners in accessing housing subsidies in New Brighton, Gqeberha, South Africa - Mgidlana, Funeka; Mbanga, Sijekula; Hamunakwadi, Purity (Frontiers in Sustainable Cities, 2025)
Assisting the poor through housing subsidies is an international practice, however, in poorer countries, homeownership has been a challenge. South Africa has been experiencing backlogs in housing emanating from several factors, such as urbanisation, rural-urban migration and population growth. These factors result in millions of people residing in informal settlements and shack backyards. Although the Finance Linked Individual Subsidy Programme (FLISP) is one of the strategies utilised by the National Department of Human Settlements to assist low-income earners in accessing housing subsidies to curb housing backlogs, positive results are yet to be achieved. This study aims to investigate the barriers to accessing housing subsidies for low-income earners residing in New Brighton, Gqerberha, an urban township in the Eastern Cape, South Africa. Utilising qualitative data from primary and secondary sources to collect the data, the interpretivism research paradigm was adopted through a case study design. The secondary data consisted of a literature review of relevant academic and policy documents such as journal articles, reports, research documents, and national policy documents. The primary data consisted of 10 face-to-face interviews with urban dwellers in informal settlements and backyard dwellers. To make sense of the data, thematic and content data analysis was used as a process and way to draw valid conclusions from text, words, and concepts. The findings show that low-income earners face multiple and interrelated barriers to accessing housing subsidies, such as a lack of national awareness campaigns or publicity campaigns on FLISP; a lack of availability of housing delivery programmes to cater for informal settlements and backyard dwellers; qualifying citizens not opting for housing subsidies and inadequate and irregular incomes. The study underscores that, while qualified individuals receive housing assistance through FLISP, the programme has not sufficiently addressed housing issues due to equity problems and a low participation rate in securing housing subsidies stemming from mixed feelings on the programme, thereby indirectly discouraging individuals from considering FLISP. Although the programme targets first-time homeowners among low-income earners, the findings emphasise that residents in New Brighton often face inadequate and irregular income, hindering their ability to obtain mortgage loans and property. The article concludes by proffering recommendations and implications for policy and practice. The study proposes improving the design, delivery, and monitoring of housing subsidy programmes by the National Department of Human Settlements and other stakeholders to enhance their capacity to liaise and coordinate the FLISP programme for better outcomes in low-income households and communities.